(untitled) (Revista de Diavulgación L’esprit Ingénieux, 2017)
This document collects bibliographic information about the origin, action and damages that salts cause in the materials used in civil engineering. An approach is made to concepts such as: salts, crystallization of salts, efflorescence in ceramic masonry, salt deposits, more frequent efflorescence and a compilation of the main damages caused by salts in building materials such as alveolization, fracturing, disintegration, corrosion by chlorides and sulphate attacks. Finally, a series of case examples are shown in which the presence of salts has caused damage to construction materials and rocks. It was concluded that the construction materials are susceptible to deterioration by the presence of salts, either in chemical attacks by the interaction of sulfates and chlorides with the materials, as in physical attacks mainly by the crystallization and hydration of salts present in the pores of the materials; are those that have a higher coefficient of capillary absorption and greater porosity.